Sintesis dan Karakterisasi Senyawa Ion Tembaga (II) Sulfat (CuSO₄) melalui Reaksi Tembaga (II) Oksida dengan Asam Sulfat - Iis Siti Jahro; Erniati Zai; Julia Putri Santi Waruwu; Romauli Magdalena Manik S; Theresia Valesita Simamora (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to synthesize and characterize copper(II) sulfate pentahydrate (CuSO4·5H2O) through a simple practical method that is suitable for application in educational laboratories. The synthesis was carried out through a neutralization reaction between copper(II) oxide (CuO) and dilute sulfuric acid (H2SO4 2M), followed by heating at a temperature of ±70°C, gravity filtration, temperature crystallization using ice cubes, and drying at room temperature. Characterization was carried out visually on the color and shape of the crystals formed. The synthesis results in a characteristic blue crystal with an actual mass of 0.73 grams. The yield calculation using Mr CuSO4·5H2O (249.5 g/mol) resulted in a yield of 11.7%. The relatively low yield is influenced by the small reaction scale, product loss during the process, and suboptimal crystallization conditions. his method can be an alternative for undergraduate educational practicums, although optimization of reaction conditions is still needed.